PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI ALFAMART KOTA SORONG - Sari Faraswati Jewahan; Andrey Maryen; james Kastanya (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze the effect of service quality on customer satisfaction at Alfamart Sorong City. This type of research is quantitative. This research was conducted at Alfamart Sorong City in July 2022. The population in the study amounted to 125 customers. The research sample was 55 respondents. There are 2 sources of data used, namely primary data and secondary data. The data collection technique used is a questionnaire. The data analysis technique used is simple linear regression analysis test, t-test, and coefficient of determination test. The results showed that the calculation of the simple regression coefficient showed that the value of the constant coefficient was 4.666, the coefficient of the independent variable (X) was 0.511. So that the regression equation Y=4.666+0.511X is obtained, the value of the t-count hypothesis is greater than the t-table value, namely 4.215 > 2.460 with a significance level of 0.000 <0.05, and the coefficient of determination test shows the adjusted R square value of 0.240 or 24.0 %. This means that the quality of service affects customer satisfaction at Alfamart in Sorong City 24.0%.